Genome-Wide Analysis of Differentially Expressed miRNAs and Their Associated Regulatory Networks in Lenses Deficient for the Congenital Cataract-Linked Tudor Domain Containing Protein TDRD7 - Anand, Deepti; Al Saai, Salma; Shrestha, Sanjaya K.; Barnum, Carrie E.; Chuma, Shinichiro; Lachke, Salil A. (Frontiers in Cell and Developmental Biology, 2021)
Mutations/deficiency of TDRD7, encoding a tudor domain protein involved in post-transcriptional gene expression control, causes early-onset cataract in humans. While Tdrd7 is implicated in the control of key lens mRNAs, the impact of Tdrd7 deficiency on microRNAs (miRNAs) and how this contributes to transcriptome misexpression and to cataracts, is undefined. We address this critical knowledge-gap by investigating Tdrd7-targeted knockout (Tdrd7-/-) mice that exhibit fully penetrant juvenile cataracts. We performed Affymetrix miRNA 3.0 microarray analysis on Tdrd7-/- mouse lenses at postnatal day (P) 4, a stage preceding cataract formation. This analysis identifies 22 miRNAs (14 over-expressed (miR-15a, miR-19a, miR-138, miR-328, miR-339, miR-345, miR-378b, miR-384, miR-467a, miR-1224, miR-1935, miR-1946a, miR-3102, miR-3107), 8 reduced (let-7b, miR-34c, miR-298, miR-382, miR-409, miR-1198, miR-1947, miR-3092)) to be significantly misexpressed (fold-change ≥ ±1.2, p-value < 0.05) in Tdrd7-/- lenses. To understand how these misexpressed miRNAs impact Tdrd7-/- cataract, we predicted their mRNA targets and examined their misexpression upon Tdrd7-deficiency by performing comparative transcriptomics analysis on P4 and P30 Tdrd7-/- lens. To prioritize these target mRNAs, we used various stringency filters (e.g. fold-change in Tdrd7-/- lens, iSyTE-based lens-enriched expression) and identified 98 reduced and 89 elevated mRNA targets for overexpressed and reduced miRNAs, respectively, which were classified as “top-priority”, “high-priority” and “promising” candidates. For Tdrd7-/- lens overexpressed miRNAs, this approach identified 18 top-priority reduced target mRNAs: Alad, Ankrd46, Ceacam10, Dgat2, Ednrb, H2-Eb1, Klhl22, Lin7a, Loxl1, Lpin1, Npc1, Olfm1, Ppm1e, Ppp1r1a, Rgs8, Shisa4, Snx22 and Wnk2. Majority of these targets were also altered in other gene-specific perturbation mouse models (e.g. Brg1, E2f1/E2f2/E2f3, Foxe3, Hsf4, Klf4, Mafg/Mafk, Notch) of lens defects/cataract, suggesting their importance to lens biology. Gene ontology (GO) provided further insight into their relevance to lens pathology. For example, the Tdrd7-deficient lens capsule defect may be explained by reduced mRNA targets (e.g. Col4a3, Loxl1, Timp2, Timp3) associated with “basement membrane”. GO analysis also identified new genes (e.g. Casz1, Rasgrp1) recently linked to lens biology/pathology. Together, these analyses define a new Tdrd7-downstream miRNA-mRNA network, in turn, uncovering several new mRNA targets and their associated pathways relevant to lens biology and offering molecular insights into the pathology of congenital cataract.